If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = 10x + 3 Reorder the terms: 9 + 4x = 10x + 3 Reorder the terms: 9 + 4x = 3 + 10x Solving 9 + 4x = 3 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 9 + 4x + -10x = 3 + 10x + -10x Combine like terms: 4x + -10x = -6x 9 + -6x = 3 + 10x + -10x Combine like terms: 10x + -10x = 0 9 + -6x = 3 + 0 9 + -6x = 3 Add '-9' to each side of the equation. 9 + -9 + -6x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = 3 + -9 -6x = 3 + -9 Combine like terms: 3 + -9 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| -59=-4n-3 | | 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 | | 12x+32=10+y | | 2y^2-6x+1=0 | | 3m^3+192= | | -70=14n | | 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 | | -9x+1=2x-8 | | 3(y-6)=8y+22 | | P-3=11 | | 7+4=27 | | 6x+9=-4 | | N-3=-21 | | 2cosx=2-3sinx | | N-3=-23 | | -5w+3(w+5)=27 | | N^2+3n-128=0 | | K+12=1 | | 30-10x=-7(6-x) | | 7h+9=32 | | 19=a+1 | | 6p-6+40p=2+34p |